Hubungan Pengajaran Mata Kuliah Ekonomi Islam terhadap Minat Mahasiswa Menabung di Bank Syariah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2017)
This study aims to examine the relationship between teaching of Islamic Economics courses in college and the interest of students to save in Islamic Bank. This is a descriptive-quantitative research by taking a case study of STIE Ahmad Dahlan Jakarta students. The study concluded that there is a significant relationship between the material of Islamic Economics, the intensity of learning , and students' understanding to imcrease the interest of students to save in Islamic Bank.